Ta’tsīru Ṭarīqati Ta‘Līm Al-Kamm ‘Alā Itqān Al-Mufradāt Ladā At-Talāmīdh Bi Al-Madrasah Ats-Tsānawiyyah Al-Islāmiyyah Al-Falāḥ Jāmbī: تأثير طريقة تعليم الكم على إتقان المفردات لدى التلاميذ بالمدرسة الثانوية الإسلامية الفلاح جامبي - Qodri, Muhammad; Zulmi Marisa (Prodi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam As-Sunnah, 2025)
This study is motivated by the difficulty of students understanding every Arabic word due to the lack of vocabulary they have, the use of inappropriate methods which has an impact on their mastery of Arabic vocabulary. This study is comparative quantitative research with an experimental type, using tests, documentation, with natural test analysis methods & hypothesis testing. The findings are : The results of vocabulary mastery using the experimental class obtained the largest value of 100, the smallest value of 55, and the equation 83.45. The results of vocabulary mastery without using the control class were the highest score 100, the smallest score 20, the equation 67.93. This means that the results of mastering Arabic vocabulary using the quantity teaching method are greater than the results of students mastering Arabic vocabulary without the quantum teaching method. This shows that there is a big difference between the results of mastering Arabic vocabulary between students who use quantitative methods and those who do not use quantitative methods. Meanwhile, the effect size results are 0.915 with a rate of 82%, meaning that the quantum teaching method has a significant influence on the results of Arabic vocabulary mastery. The conclusion of this research is that hypothesis testing uses the Independent Sample T-test with a significance result of 0.05 < 2-tailed, namely 0.001 < 0.05. The degree of influence means 0.915 which means 82%. accepted. The results show that there is a significant effect of using quantitative teaching methods in increasing Arabic vocabulary among students.